Validation and Application of an Innovative Protective Group Concept: Enhancing Substrate Reactivity in Glycosylations by Disrupting Intermolecular Interactions - Yano, Kumpei; Yoshimoto, Takuya; Tsutsui, Masato; Manabe, Yoshiyuki; Fukase, Koichi (Synlett, 2024)
We have established an innovative protective approach that disrupts intermolecular interactions to enhance substrate reactivity. Specifically, diacetylimide protection of acetamide prevents the formation of hydrogen bonds, while the incorporation of tert-butyl groups on the aromatic protecting group disrupts π-stacking interactions, both of which culminate in heightened reactivity in glycosylations. We explored the synergistic implementation of these protective measures and applied them to the synthesis of 6-sulfo sialyl Lewis X.
Keywords: protecting groups; intermolecular interactions; glycan synthesis; 6-sulfo sialyl Lewis X; sialic acid